Punitive expeditions and divine revenge: oral and colonial histories of rebellion and Pacification in western Borneo, 1886–1902 - Wadley, R.L. (2004)
This article presents different accounts of two events in the efforts of Dutch and British colonial authorities to pacify the Iban within their respective territories on the island of Borneo; namely, it presents both the Dutch and British reports of the punitive expeditions in 1886 and 1902 against rebellious Iban headhunters and the oral historical narratives of the Iban today. In addition to providing historical and cultural background to Iban resistance to pacification, it spells out the Iban conception of the past and fragmentation of related narratives. The weight that the oral accounts place on these two events is discussed in that light, with the Iban viewing their colonial experience as the struggle of spiritual forces allied with both the Iban and the European.